Implementasi Metode Storytelling Berbasis Materi Moderasi Beragama dalam Meningkatkan Kecakapan Berbicara Siswa Sekolah Dasar - Muhammad; Holis, Khoirul (LP2M Universitas Islam Ahmad Dahlan, 2023)
Children are a gift from Allah Swt. to be cared for, raised and cared for with love so that one day they become perfect human beings, useful for religion, nation and state. Through education, children are expected to maximize their potential. Elementary school education in general is education that is held to encourage the growth and development of children as a whole, both from the aspect of intelligence and personality. The purpose of this study was to examine the level of children's speaking skills through the storytelling learning model at SDI Nurul Amin Rek Kerrek. The research method uses a qualitative type with a case study approach. There were 10 research subjects consisting of 4 men and 6 women. Data sources are primary and secondary. Data collection techniques through observation and documentation. Data analysis uses Miles-Huberman analysis which consists of data reduction, data display, and plotting. The results of the study show that the Storytelling learning model can improve children's speaking skills at the elementary school level.